1998
DOI: 10.1076/jcen.20.5.684.1131
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Function in Patients with Nasopharyngeal Carcinoma after Radiotherapy

Abstract: A neuropsychological test battery was administered to 27 adult patients with nasopharyngeal carcinoma (NPC) who had received radiotherapy, 28 adult patients with NPC awaiting radiotherapy, and 35 normal adult controls. The 27 patients with radiotherapy had a conventional dosage, 220 cGy per fraction, or less. The median interval between the completion of radiotherapy and the evaluation of neuropsychological function was 1.7 years. Groups were matched for age and educational level. The results showed that our N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 10 publications
1
33
1
Order By: Relevance
“…Six studies [8][9][10][11][12][13] evaluated the neurocognitive effects of potential radiation-induced brain injury. The study samples included only patients with either nasopharyngeal or paranasal sinus tumors, in which treatment entailed incidental radiation to normal brain tissue and thus the potential for direct radiation damage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies [8][9][10][11][12][13] evaluated the neurocognitive effects of potential radiation-induced brain injury. The study samples included only patients with either nasopharyngeal or paranasal sinus tumors, in which treatment entailed incidental radiation to normal brain tissue and thus the potential for direct radiation damage.…”
Section: Introductionmentioning
confidence: 99%
“…The studies also have other methodological limitations. Five studies [8,9,[11][12][13] used cross-sectional designs with only posttreatment neurocognitive assessments with varied control groups and inconsistent posttreatment assessment time points ranging from 7 days to 30 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al [35] reported that NPC patients with radiation-induced brain injury (RI) exhibited negative emotions, impaired cognitive function and quality of life (QOL). The accumulated studies showed that the radiation-induced functional impairments included the disorder of short-term memory [36], personality changes [37] and motor abilities [38], a marked anterograde memory impairment for verbal material [39], neuropsychological impairments in recent memory, immediate and delayed verbal recall, and immediate visual recall [40].…”
Section: Resultsmentioning
confidence: 99%
“…Those changed regions, located in the memory and emotional network, might related with the clinical manifestations of the memory of patients with NPC after radiotherapy. Studies showed that the radiation-induced functional impairments included the disorder of short-term memory [26], personality changes [36], a marked anterograde memory impairment for verbal material [37], and neuropsychological impairments in recent memory, immediate and delayed verbal recall and immediate visual recall [38].…”
Section: Hub Regions In Post-rt-related Networkmentioning
confidence: 99%